Plasticity in the dynamic pain connectome associated with ketamine-induced neuropathic pain relief. Issue 7 (July 2019) - Rogachov, Anton; Bhatia, Anuj; Cheng, Joshua C.; Bosma, Rachael L.; Kim, Junseok A.; Osborne, Natalie R.; Hemington, Kasey S.; Venkatraghavan, Lakshmikumar; Davis, Karen D.
Abstract : Abstract: Therapeutic interventions for neuropathic pain, such as the N -methyl-D-aspartate (NMDA) antagonist ketamine, can vary widely in effectiveness. In this study, we conducted a longitudinal functional MRI study to test the hypothesis that the pain-relieving effect of ketamine is the result of reversal of abnormalities in regional low-frequency brain oscillations (LFOs) and abnormal cross-network functional connectivity (FC) of the dynamic pain connectome. We found that (1) ketamine decreased regional LFOs in the posterior cingulate cortex of the default mode network, (2) a machine-learning algorithm demonstrated that treatment-induced brain changes could be used to make generalizable inferences about pain relief, (3) treatment responders exhibited a significant decrease in cross-network static FC between the posterior cingulate cortex and regions of the sensorimotor and salience networks following treatment, (4) the degree of reduced cross-network FC correlated with the amount of pain relief, and (5) ketamine treatment did not produce significant differences in static or dynamic FC within the ascending nociceptive or descending antinociceptive pathway. These findings support the proposition that regional LFOs contribute to cross-network connectivity that underlie the effectiveness of ketamine to produce significant relief from neuropathic pain. Together with our recent findings that pretreatment dynamic FC of the descending antinociceptive pathway can predict ketamine treatment outcomes, these new findings indicate that pain relief from ketamine arises from a combination of flexible pretreatment FC of the descending antinocieptive pathway together with plasticity (reduction) of cross-network connectivity of the default mode network with sensorimotor and salience networks. Abstract : Pain relief following ketamine treatment for neuropathic pain was associated with the reversal of aberrant regional brain oscillations and cross-network functional connectivity.